The reliability of cutaneous low‐frequency oscillations in young healthy males. (29th April 2019) - Hodges, Gary J.; Mallette, Matthew M.; Cheung, Stephen S.
Abstract: Objective: Spectral analyses of laser‐Doppler flowmetry measures enable a simple and non‐invasive method to investigate mechanisms regulating skin blood flow. We assessed within‐day and day‐to‐day variability of cutaneous spectral analyses. Methods: Eleven young, healthy males were tested twice in three identical sessions, with 19 to 24 days between visits, for a total of six tests. Wavelet data were analyzed at rest, in response to local skin heating to 42 and 44°C, and during 5‐minutes PORH. We did this for six frequency bands commonly associated with physiological functions. To assess reliability, we calculated CV and ICC scores. Results: At rest, mean CV for the wavelet data ranged from 21% to 24% and ICC scores ranged from 0.67 to 0.91. During local heating, mean CV scores ranged from 17% to 22% and mean ICC scores ranged from 0.71 to 0.95. For peak PORH, CV ranged from 14% to 23% and the ICC range was 0.88 to 0.97. For the area under the curve of the PORH, CV range was 12% to 21% and ICC range was 0.81 to 0.92. Conclusions: These analyses indicate good‐to‐excellent reliability of the wavelet data in healthy young males.